SLOW BREEDING AND TRANSMUTATION PROCESS IN LOW FLUX REACTOR - Žagar, Tomaž; Magill, Joseph (Journal of Energy Technology, 2024)
This work presents the physics of selfͲsustained critical reactor operating at very low constant neutron flux. It is shown, that such reactor is a breeder and a clean reactor, not producing any higher actinides. Fossil fission reactors in Gabon were found to be natural analogues of such reactors. On the basis of these results, the concept of active repository is proposed and studied. It is shown that this concept has a very limited practical application.